Evaluasi Kelengkapan Data Informasi terkait Survei Kelas Rawat Inap Standar (KRIS) untuk Mendukung Keputusan Kesehatan di Dinas Kesehatan Sleman - Ika Putri Salsabila; Nur Rokhman; Etylusfina Etylusfina (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
This research aims to identify the completeness of information data related to the Standard Inpatient Class Survey (KRIS) at the Online Hospital (RS Online) of the Sleman Health Office and analyze its implications for decision-making in the health sector. The research method employed is a qualitative descriptive approach with in-depth data analysis from the RS Online website and related literature. Challenges faced include enhancing awareness and involvement of hospitals in data collection and reporting, as well as adapting to changes in regulations and technology. Therefore, continuous efforts are required to update policies and strategies to address these issues. The study concludes that all hospitals have completed the KRIS survey instruments, but some hospitals still need to complete identity data related to the PIC. Despite progress in data reporting, further attention is needed to enhance awareness and involvement of relevant parties and to adapt to environmental changes.